Lactate dehydrogenase: a marker of diminished antitumor immunity. (1st January 2020) - Van Wilpe, Sandra; Koornstra, Rutger; Den Brok, Martijn; De Groot, Jan Willem; Blank, Christian; De Vries, Jolanda; Gerritsen, Winald; Mehra, Niven
ABSTRACT: Lactate dehydrogenase (LDH) levels are inversely related with response to checkpoint inhibitors. Elevated LDH levels are the product of enhanced glycolytic activity of the tumor and tumor necrosis due to hypoxia, the latter being associated with high tumor burden. In this review, we elucidate the effects of glycolysis and hypoxia on antitumor immunity and set forth ways to improve response to immunotherapy in cancer patients with elevated LDH levels. We discuss the current knowledge on combining immunotherapy with glycolysis inhibitors, anti-acidifying drugs, anti-angiogenic or cytoreductive therapy.